The effect of financial compensation on health outcomes following musculoskeletal injury: systematic review. - Darnel F Murgatroyd; Petrina P Casey; Ian D Cameron; Ian A Harris (PLoS ONE)
The effect of financial compensation on health outcomes following musculoskeletal injury requires further exploration because results to date are varied and controversial. This systematic review identifies compensation related factors associated with poorer health outcomes following musculoskeletal injury. Searches were conducted using electronic medical journal databases (Medline, CINAHL, Embase, Informit, Web of Science) for prospective studies published up to October 2012. Selection criteria included: prognostic factors associated with validated health outcomes; six or more months follow up; and multivariate statistical analysis. Studies solely measuring return to work outcomes were excluded. Twenty nine articles were synthesised and then assessed using GRADE (Grading of Recommendations Assessment, Development and Evaluation) methodology to determine evidence levels. The results were mixed. There was strong evidence of an association between compensation status and poorer psychological function; and legal representation and poorer physical function. There was moderate evidence of an association between compensation status and poorer physical function; and legal representation and poorer psychological function. There was limited evidence of an association between compensation status and increased pain. In seven studies the association depended on the outcome measured. No studies reported an association between compensation related factors and improved health outcomes. Further research is needed to find plausible reasons why compensation related factors are associated with poorer health following musculoskeletal injury.